The Contribution of Dynamic Exploration to Virtual Anatomical Learning. (22nd April 2011) - Luursema, Jan-Maarten; Verwey, Willem B.
Abstract : Virtual Learning Environments are increasingly becoming part of the medical curriculum. In a previous study we (luursema et al., 2006) found that a combination of computer-implemented stereopsis (visual depth through seeing with both eyes) and dynamic exploration (being able to continuously change one's viewpoint relative to the studied objects in real time) is beneficial to anatomical learning, especially for subjects of low visuo spatial ability (the ability to form, retrieve, and manipulate mental representations of a visuo-spatial nature). A follow-up study (luursema et al., 2008) found the contribution of computer-implemented stereopsis to this effect to be small but significant. The present experiment investigated the contribution of dynamic exploration to anatomical learning by means of a virtual learning environment. Seventy participants were tested for visuo-spatial ability and were grouped in pairs matched for this ability. One individual of the pair actively manipulated a 3D reconstruction of the human abdomen; the other individual passively watched the interactions of the first individual on a separate screen. Learning was assessed by two anatomical learning tests. Dynamic exploration provided a small but significant benefit to anatomical learning.